Avaliação de métodos de inoculação de Gibberella zeae em espigas de milho - Nascimento, Josiel Pereira (2009)
The non tillage planting and the cultivation of safrinha (short season) corn are factors that may provide alterations in the microclimate and in the biology of agro ecosystem, increasing the populations of fungus like Gibberella zeae, which is the etiologic agent of one of the maize ear rots. This work had the objective to identify inoculation methods that can be useful in the election and in the characterization of genotypes tolerant to G. zeae. The experiment was conducted in Toledo/PR during the 2008 safrinha season in a randomized complete block design with five replications, on a factorial scheme where hybrids were the first factor (2B710; 30F45; DKB 214; 30F98; DKB 390; GAC 9020; 30F80; 30R50 and 30K73) and the inoculation methods were the second factor. The hybrids had been grouped as susceptible (2B710; 30F45; DKB 214; 30K73), tolerant (DKB 390; GAC 9020; 30F80; 30R50) and moderately susceptible to giberela (30F98). The 12 evaluated methods consisted of simulating the fungus natural infection on the silk or on the damage caused by insects in the lateral of the ears, and also varying by the absence of covering on the ear (humid chamber), by covering the ear for 24 hours and by covering the ear for 48. The methods with inoculation of 2 mL in the lateral of the ear without covering (3), with covering for 24 hours (7) and with covering for 48 hours (11) had shown efficiency in the characterization of tolerant and susceptible hybrids and could be used on a large scale in the identification and selection of maize varieties with tolerance to ear rot caused by G. zeae. As a result, the seed industry can provide superior materials and the farmers will reduce their losses due to kernel quality. Moreover, the whole society will consume better maize products, with less mycotoxins